High-refractive-index polyarylester containing thiophene structure and preparation method of high-refractive-index polyarylester

Through the copolymerization reaction of thiophene diacyl chloride and cardocyclic aromatic bisphenol, high refractive index polyaryl esters were prepared, which solved the problems of high-temperature injection molding materials in the prior art, and achieved high refractive index and good quality Optical material with transmittance, suitable for high-pixel lenses.

CN119119442AActive Publication Date: 2024-12-13DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411259797.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-13
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

The existing high-refractive index optical resins have high material melting fingers and are yellowish in high temperature injection molding, making it difficult to meet the needs of high-pixel and high-resolution lenses.

Method used

The high refractive index polyarylate with a thiophene-containing structure is used to react 2,5-thiophene dicarboxylic acid with sulfoxide chloride to form thiophene diacyl chloride, and copolymerize with cardocyclic aromatic bisphenol to prepare a high refractive index and good high temperature. Fluid polyaryl.

Benefits of technology

The refractive index at 589nm reaches 1.64-1.69, the glass transition temperature is 220-300℃, and the visible light transmittance is ≥88%, which is suitable for high-performance optical lenses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119442A_ABST
    Figure CN119119442A_ABST
Patent Text Reader

Abstract

The invention discloses a high refractive index polyarylester containing a thiophene structure, the polyarylester has a structure represented by a formula I: # imgabs0 #, in the formula I, R is selected from at least one of phenolphthalein, bisphenol fluorene, bisphenol A, methyl bisphenol fluorene, biether fluorene, isoindolinone and phenolphthalein; and n is selected from 1 to 1000. The high-refractive-index optical polyester is prepared in a way of copolymerizing cardo ring-containing aromatic bisphenol and thiophene acyl chloride, the refractive index (nd) at 589nm can reach 1.64-1.69, the glass-transition temperature can reach 220-300 DEG C, the visible light transmittance is high and is greater than or equal to 88%, and the high-refractive-index optical polyester has a relatively high potential application value in the aspect of high-refractive-index optical resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a high-refractive-index polyarylate containing a thiophene structure and a preparation method thereof, and belongs to the field of polymer materials. Background Art

[0002] With the rapid development of modern science and technology, the application scope of optical lenses has penetrated into multiple fields. Resin lenses are popular due to their low manufacturing difficulty, high mass production capacity, low cost and lightweight, and are also a hot spot in the field of lens design at this stage. Taking mobile phone lenses as an example, the early mobile phone lenses were composed of only 2-4 plastic lenses. However, with the continuous evolution of the market and the guidance of the demand side, the number of lenses has reached 7 (P) and 8P. With the continuous improvement of the demand side in terms of high pixels, high resolution, large aperture, ultra-wide angle, etc., the lens module continues to develop towards high P.

[0003] High refractive index optical resin can increase the refractive index of the lens, facilitate aberration correction, and thus improve the performance of the lens. It can also reduce the height of the optical system and achieve a low total lens length (TTL), effectively realizing the miniaturization and lightweight of the lens. Currently, thermoplastic high refractive index optical resins are mainly prepared through the design of condensed ring structures, sulfur-containing structures, and phosphorus-containing structures, combined with the requirements of Abbe number, high temperature fluidity and other factors.

[0004] In addition, patent CN 200580022942.9 discloses a resin composition and a molded body thereof. Due to the strong rigidity of the condensed ring structure, the material melt index is high and is not conducive to high-temperature injection molding. The sulfur-containing structure is usually yellowish in color. This patent uses a sulfur-containing structure to prepare a high-refractive-index optical polyester by copolymerizing cardo-ring aromatic bisphenol with thiophene chloride. The refractive index at 589nm (n d ) can reach 1.64-1.69, the glass transition temperature can reach 220-300℃, it has a high visible light transmittance ≥88%, and has a high potential application value in high refractive index optical resins. Summary of the invention

[0005] According to one aspect of the present application, a high refractive index polyarylate containing a thiophene structure is provided.

[0006]

[0007] Characterized in that the polyarylate has a structure of formula I:

[0008] Formula I;

[0009] The R is selected from at least one of phenolphthalein, bisphenol fluorene, thymolphthalein, methyl bisphenol fluorene, bisether fluorene, isoindolinone, and phenolphthalein;

[0010] The n is selected from 1 to 1000.

[0011] According to a second aspect of the present application, a method for preparing a high refractive index polyarylate containing a thiophene structure is provided, comprising at least the following steps:

[0012] Step I: Mix 2,5-thiophenedicarboxylic acid and thionyl chloride, add N,N-dimethylformamide, and perform reaction I to obtain thiophenedicarboxylic acid chloride;

[0013] Step II: Disperse the thiophene dichloride obtained in step I and the cardo-ring-containing aromatic bisphenol in an organic solvent, and react with II in the presence of a catalyst to obtain a polyarylate containing a thiophene structure.

[0014] Optionally, in step I, the mass ratio of the 2,5-thiophenedicarboxylic acid to thionyl chloride is 1:2 to 1:100.

[0015] Optionally, in step I, the mass ratio of N,N-dimethylformamide to 2,5-thiophenedicarboxylic acid is 0.55:1 to 0.55:1 to 100:1.

[0016] Optionally, in step I, the reaction conditions of reaction I are as follows:

[0017] The temperature of the reaction I is 78-120°C;

[0018] The reaction time of the reaction I is 5 to 48 hours.

[0019] Optionally, in step II, the cardo-ring-containing aromatic bisphenol is selected from at least one of phenolphthalein, bisphenol fluorene ether, thymolphthalein, bisphenol fluorene, isoindolinone, methyl bisphenol fluorene, and phenolphthalein.

[0020] Optionally, in step II, the organic solvent is selected from at least one of dichloromethane, diphenyl ether, N,N-dimethylformamide, toluene, dimethylacetamide, and xylene.

[0021] Optionally, in step II, the catalyst is selected from at least one of triethylamine, nitrogen-methylimidazole, potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, sodium bicarbonate, and potassium bicarbonate.

[0022] Optionally, in step II, the molar ratio of thiophene dichloride to cardo ring-containing aromatic bisphenol monomer is 0.9:1 to 1.1:1;

[0023] The mass ratio of the catalyst to the cardo-ring-containing aromatic bisphenol monomer is 0.34:1 to 0.72:1.

[0024] Optionally, in step II, the reaction conditions of reaction II are as follows:

[0025] The reaction time of II is 2 to 5 hours;

[0026] The temperature of the reaction II is 10-170°C.

[0027] The present application discloses a method for preparing a high refractive index polyarylate containing thiophene and its application, by copolymerizing cardo-ring-containing aromatic bisphenol with thiophene acid chloride. The specific structure is as follows:

[0028] 1 The bisphenol structure containing a cardo ring can be phenolphthalein, bisphenol fluorene ether (BPEF), thymolphthalein, bisphenol fluorene, isoindolinone, methyl bisphenol fluorene, and phenolphthalein containing a cardo ring aromatic bisphenol.

[0029] The structure of thiophene dichloride is as follows:

[0030]

[0031] 2 The polymerization method can be low temperature solution, high temperature solution, interfacial polycondensation, or melt polycondensation.

[0032] 3. The bisphenol monomer in the polymer structure can be one or more of the R-substituted monomers. One or two of the acyl chloride monomers in the polymer.

[0033] 4 The catalyst selected in the polymerization process can be one or more of triethylamine, nitrogen-methylimidazole, potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, sodium bicarbonate, and potassium bicarbonate.

[0034] 5. The molar ratio of the thiophene chloride-containing monomer to the cardo ring-containing diphenol monomer in the preparation method is 0.9:1 to 1.1:1.

[0035] 6. The reaction conditions of the preparation method include temperature of 0°C to 200°C, solid content of 5% to 30%, etc.

[0036] The beneficial effects of this application include:

[0037] The thiophene polyarylate provided in the present application has a high refractive index, good high temperature fluidity, and light transmittance. The refractive index (nd) at 589nm can reach 1.64-1.69, the glass transition temperature can reach 220-300°C, and has a high visible light transmittance of ≥88%. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The refractive index and wavelength curve of the polyarylate prepared in Example 1 of the present application;

[0039] Figure 2 This is a differential scanning calorimetry curve of the polyarylate prepared in Example 2 of the present application;

[0040] Figure 3 This is a gel permeation chromatogram of the polyarylate prepared in Example 1 of the present application;

[0041] Figure 4 This is the H NMR spectrum of the polyarylate prepared in Example 1 of the present application;

[0042] Figure 5 This is the H NMR spectrum of the polyarylate prepared in Example 2 of the present application;

[0043] Figure 6 This is a thermogravimetric curve of the polyarylate prepared in Example 3 of the present application;

[0044] Figure 7 This is the H NMR spectrum of the polyarylate prepared in Example 4 of the present application;

[0045] Figure 8 is a differential scanning calorimetry curve of the polyarylate prepared in Example 5 of the present application;

[0046] Fig. 9 This is the gel permeation chromatogram of the polyarylate prepared in Example 5 of the present application. DETAILED DESCRIPTION

[0047] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0048] Unless otherwise specified, the raw materials and catalysts in the examples and comparative examples of the present application were purchased through commercial channels.

[0049] The analysis methods in the examples and comparative examples of the present application are as follows:

[0050] The molecular structures of the thiophene-containing bisphenol monomer and the thiophene-containing polyarylate synthesized in the examples were analyzed using ECZ Luminous (JNM-ECZL series, 400 MHz) nuclear magnetic resonance (NMR) hydrogen spectrometer.

[0051] The thermal properties of the thiophene-containing polyarylate synthesized in the example were analyzed using a TA DSC25 Differential Scanning Calorimeter (DSC) differential scanning calorimeter;

[0052] The molecular weight of the thiophene-containing polyarylate synthesized in the example was analyzed using a 2414 HPLC gel permeation chromatography (GPC) instrument;

[0053] The thermal stability of the thiophene-containing polyarylate synthesized in the example was analyzed using a TA Discovery TGA55 Thermogravimetric Analyzer (TGA) thermogravimetric analyzer.

[0054] Preparation Example 1

[0055] 17.22g of 2,5-thiophenedicarboxylic acid and 118.97g of thionyl chloride were added to a 250mL round-bottom flask equipped with a tail gas absorber and a condenser, wherein the tail gas absorber was a NaOH aqueous solution, and the temperature was raised to 78°C, and 10mL of N,N-dimethylformamide was slowly added dropwise to the system, and the reaction was continued for 20h after the addition was completed. The excess thionyl chloride was then removed by vacuum distillation, and a yellow oily product was finally obtained, namely, thiophenedicarboxylic acid chloride.

[0056] Preparation Example 2

[0057] 17.22g of 2,5-thiophenedicarboxylic acid and 118.97g of thionyl chloride were added to a 250mL three-necked flask equipped with a tail gas absorber, a condenser and a nitrogen inlet, wherein the tail gas absorber was a NaOH aqueous solution, and the temperature was raised to 78°C, and 10mL of N,N-dimethylformamide was slowly added dropwise to the system, and the reaction was continued for 20h after the addition was completed. 20mL of toluene was added, and the excess thionyl chloride and toluene were removed by vacuum distillation, and the process was repeated several times to finally obtain a yellow oily product, namely, thiophenedicarboxylic acid chloride.

[0058] Example 1

[0059] 3.18g of phenolphthalein, 3mL of triethylamine and 40mL of dichloromethane were added to a 250mL three-necked flask with mechanical stirring, condensation reflux and nitrogen inlet, and stirred for 3h. Then 2.17g of thiophene dichloride obtained in Preparation Example 1 was dissolved in 40mL of dichloromethane solution and added to the reaction flask, and the reaction was continued at 10°C for 3h. The reaction solution was sunk into anhydrous methanol, and the precipitate was washed once with anhydrous methanol, filtered and dried to obtain polyarylate. The H NMR spectrum of the polyarylate was shown as Figure 4 The corresponding integrated area ratio of the proton peaks in different chemical environments corresponds to that of the polymer. The single peak near 7.96 ppm belongs to the two separate proton peaks on the thiophene ring, and the double peak near 8 ppm is the characteristic proton peak on the benzene ring of the phenolphthalein group close to the ester bond. The gel permeation chromatography of the polyarylate shows Figure 3 The number average molecular weight is 24.05 kg / mol, indicating the successful preparation of polyarylate. The visible light transmittance, glass transition temperature and refractive index of the obtained polyarylate are shown in the relevant data table 1. The refractive index and wavelength curve of the polyarylate is shown in Figure 1 ,like Figure 1 A typical image of the refractive index changing with wavelength is shown in FIG. , and the refractive index is 1.6950 at 589 nm, indicating that it is a high-refractive-index optical material with excellent performance.

[0060] Example 2

[0061] 4.31g of thymolphthalein, 18.80mg of phenol, 3mL of nitrogen-methylimidazole and 40mL of dichloromethane were added to a 250mL three-necked flask with mechanical stirring, condensation reflux and nitrogen inlet, and stirred for 3h. Then 2.19g of thiophene dichloride obtained in Preparation Example 2 was dissolved in 40mL of dichloromethane solution and added to the reaction flask, and the reaction was continued at 20°C for 3h. The reaction solution was sunk into anhydrous methanol, and the precipitate was washed once with anhydrous methanol, filtered and dried to obtain polyarylate. The H NMR spectrum of the polyarylate was shown as Figure 5 The corresponding integrated area ratio of the proton peaks in different chemical environments corresponds to that of the polymer. The single peak near 7.96ppm belongs to two separate proton peaks on the thiophene ring, and the peak between 7.0-7.5ppm is the proton peak on the aromatic ring of typical thymolphthalein, indicating the successful preparation of polyarylate. The data related to the visible light transmittance, glass transition temperature, and refractive index of the obtained polyarylate are shown in Table 1. The differential scanning calorimetry curve of the polyarylate is shown in Figure 2 The curve of the polyarylate obtained in the embodiment has only one typical glass transition process, the glass transition temperature is 229.8°C, there is no crystallization behavior, and it is an amorphous structure.

[0062] Example 3

[0063] 3.93 g of isoindolinone, 21.68 mg of phenol, 3 mL of triethylamine and 40 mL of dichloromethane were added to a 250 mL three-necked flask with mechanical stirring, condensation reflux and nitrogen inlet, and stirred for 3 hours. Then 2.19 g of thiophene dichloride obtained in Preparation Example 1 was dissolved in 40 mL of dichloromethane solution and added to the reaction flask, and the reaction was continued at 10°C for 3 hours. The reaction solution was sunk into anhydrous methanol, and the precipitate was washed once with anhydrous methanol, filtered and dried to obtain polyarylate. The thermogravimetric curve of the polyarylate is shown in Figure 6 The 5% thermal decomposition temperature of the polymer is above 400°C, indicating that the obtained polyarylate has good thermal stability. The data related to the visible light transmittance, glass transition temperature and refractive index of the obtained polyarylate are shown in Table 1.

[0064] Example 4

[0065] 3.50 g of bisphenol fluorene, 42.46 mg of 4-cinnamic phenol, 1.21 g of sodium hydroxide, 80 mL of deionized water and a small amount of benzyltriethylammonium chloride were added to a 500 mL three-necked flask equipped with mechanical stirring, condensation reflux and nitrogen inlet, and stirred until the system was clear. 2.19 g of thiophene dichloride obtained in Preparation Example 2 was dissolved in 60 mL of dichloromethane solution, and slowly added dropwise to the rapidly stirred alkaline solution of bisphenol monomer, and reacted at 10°C for 2 hours. It was sunk into a hydrochloric acid / methanol (volume ratio: 1 / 50) solution, and the filtered solid was washed with deionized water for 3 to 5 times, and dried to obtain polyarylate. The nuclear magnetic hydrogen spectrum of the polyarylate was shown in Figure 7The corresponding integral area ratio of the proton peaks in different chemical environments corresponds to that of the polymer. The two double peaks between 7.0-7.3ppm are the proton peaks on the two benzene rings near the ester bond of the bisphenol fluorene group, and the single peak near 7.96ppm belongs to the two separate proton peaks on the thiophene ring, indicating the successful preparation of polyarylate. The data on the visible light transmittance, glass transition temperature, and refractive index of the obtained polyarylate are shown in Table 1.

[0066] Example 5

[0067] 4.39g of bisphenol fluorene ether (BPEF), 20g of diphenyl ether, and 2.17g of thiophene dichloride obtained in Preparation Example 2 were placed in a 250mL three-necked flask equipped with a nitrogen inlet, mechanical stirring, and condensation reflux, and the temperature was raised to 170°C for reaction for 5h. After the reaction was completed, the reaction liquid was cooled to 60°C and immersed in anhydrous methanol. The product was filtered and washed once with anhydrous methanol, and then dried to obtain a polyarylate product. The differential scanning calorimetry curve of the polyarylate is shown in Figure 8 In the differential scanning calorimetry curve, only one obvious and typical glass transition process can be seen, and no crystallization behavior is observed, indicating that the polyarylate is an amorphous structure. The permeation chromatography of the polyarylate shows Fig. 9 The number average molecular weight is 23.75 kg / mol, indicating the successful preparation of polyarylate. The data related to visible light transmittance, glass transition temperature and refractive index of the obtained polyarylate are shown in Table 1.

[0068] Comparative Example 1

[0069] 3.18g of phenolphthalein, 2.17g of thiophene dichloride, 20mL of dichloromethane, and 1mL of triethylamine were placed in a 250mL nitrogen inlet, mechanically stirred, and reacted at low temperature of 10°C for 5h. After the reaction, it was sunk into anhydrous methanol, filtered, and the product was washed once with anhydrous methanol, and then dried to obtain a polyarylate product. The visible light transmittance, glass transition temperature, and refractive index of the obtained polyarylate are shown in Table 1.

[0070] Table 1 Visible light transmittance, glass transition temperature, and refractive index of synthesized polyarylate containing thiophene

[0071] Example 1 89 226.3 1.648 Example 2 88 229.1 1.689 Example 3 88 247.3 1.658 Example 4 88 260.9 1.663 Example 5 89 295.7 1.671 Comparative Example 1 86 273.4 1.632

[0072] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A high refractive index polyarylate containing a thiophene structure, characterized in that: The polyarylate has the structure of Formula I: In Formula I, The R is selected from at least one of phenolphthalein, bisphenol fluorene, thymolphthalein, methyl bisphenol fluorene, bisether fluorene, isoindolinone, and phenolphthalein; The n is selected from 1 to 1000.

2. The method for preparing the high refractive index polyarylate containing thiophene structure according to claim 1, characterized in that: At least the following steps are included: Step I: Mix 2,5-thiophenedicarboxylic acid and thionyl chloride, add N,N-dimethylformamide, and perform reaction I to obtain thiophenedicarboxylic acid chloride; Step II: Disperse the thiophene dichloride obtained in step I and the cardo-ring-containing aromatic bisphenol in an organic solvent, and react with II in the presence of a catalyst to obtain a polyarylate containing a thiophene structure.

3. The preparation method according to claim 2, characterized in that: In step I, the mass ratio of the 2,5-thiophenedicarboxylic acid to thionyl chloride is 1:2 to 1:

100.

4. The preparation method according to claim 2, characterized in that: In step I, the mass ratio of N,N-dimethylformamide to 2,5-thiophenedicarboxylic acid is 0.55:1 to 100:

1.

5. The preparation method according to claim 2, characterized in that: In step I, the reaction conditions of reaction I are as follows: The temperature of the reaction I is 78-120°C; The reaction time of the reaction I is 5 to 48 hours.

6. The preparation method according to claim 2, characterized in that: In step II, the cardo ring-containing aromatic bisphenol is selected from at least one of phenolphthalein, bisphenol fluorene ether, thymolphthalein, bisphenol fluorene, isoindolinone, methyl bisphenol fluorene, and phenolphthalein.

7. The preparation method according to claim 2, characterized in that: In step II, the organic solvent is selected from at least one of dichloromethane, diphenyl ether, N,N-dimethylformamide, toluene, dimethylacetamide, and xylene.

8. The preparation method according to claim 2, characterized in that: In step II, the catalyst is selected from at least one of triethylamine, nitrogen-methylimidazole, potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, sodium bicarbonate, and potassium bicarbonate.

9. The preparation method according to claim 2, characterized in that: In step II, the molar ratio of the thiophene dichloride to the cardo ring-containing aromatic bisphenol monomer is 0.9:1 to 1.1:1; The mass ratio of the catalyst to the cardo-ring-containing aromatic bisphenol monomer is 0.34:1 to 0.72:

1.

10. The preparation method according to claim 2, characterized in that: In step II, the reaction conditions of reaction II are as follows: The reaction time of II is 2 to 5 hours; The temperature of the reaction II is 10-170°C.

Citation Information

Patent Citations

  • Resin composition and molded object thereof

    CN101018824A

  • Polyester resin or polyester carbonate resin, and optical member using resin

    CN111655754A

  • Thiophene compound, synthesis method thereof and composition containing thiophene compound

    CN118201912A

  • Birefringent film and polarization element

    JP2009175300A

  • Polyarylate resin having fluorene skeleton

    JP2012131865A